Performance of Acacia mangium-Cow Pea Based Agroforestry System in North Central Plateau Zone of Odisha - Shial, G.; Nayak, U. S.; Upadhyay, K. (International Journal of Bio-resource and Stress Management, 2017)
Field experiments carried out to assess the performance of Acacia mangium-Cow pea based agroforestry system and their interactive effects on the growth of tree species and yield of intercrop at Keonjhar district of Odisha during 2010 to 2012. The results indicated that the growth and establishment of Acacia mangium plants were found to be superior in the intercropped plots than the un-cropped plots. At 36 months after planting, the Acacia mangium plants under agro-forestry system registered better crop growth (7.68 m height, 12.88 cm DBH, 3.45 m crown spread, 32.34 no. of branches plant-1, 0.092 t ha-1 pruned biomass) as compared to the pure crop (7.14 m height, 12.45 cm DBH, 3.34 m crown spread, 31.78 no. of branches plant-1 and 0.086 t ha-1 pruned biomass). The yield of cow pea as intercrop was not so much affected by the growth of Mangium plants with a marginal yield reduction from 20.75 q ha-1 during first year to 18.90 q ha-1 in the 3rd year. The Acacia mangium-cow pea agroforestry system also resulted in an additional return of ` 9050.00 ha-1 during the first year to ` 7200.00 ha-1 during the third year from the harvest of cow pea. Hence, growing cow pea in the interspaces of Acacia mangium tree can be an ideal agroforestry system for the rainfed upland regions of this agro-climatic zone